Analisis Kasus Penembakan Pesawat Udara Ukraina oleh Militer Iran - Irma Halimah Hanafi (Fakultas Hukum Universitas Pattimura, 2021)
Introductioan: Aviation is an activity that many people are interested in at this time, because it can cover one place in a fast time. In international law, aviation is divided into civil aviation and military aviation. The shooting down of the Ukrainian plane by the Iranian military is a unique case because the one shot was a scheduled civilian plane flying over the airspace of a country that is at war or armed conflict.Purposes of the Research: Therefore, the purpose of this paper is to analyze in depth how international air law regulates the shooting of civilian aircraft in the airspace of countries that are in situations of war or armed conflict.Methods of the Research: by using normative legal research methods that use secondary data consists of primary, secondary and tertiary legal materials with a statutory approach and historical approach.Results of the Research: The result of this paper is that the shooting of a civilian aircraft gives a lesson that in situations of war and armed conflict, Countries involved in war or armed conflict should establish a no-fly zone in their airspace and notify the international community about their country being in a state of war or armed conflict.